Co-sputtering of gold and copper onto liquids: a route towards the production of porous gold nanoparticles - Chauvin, Adrien; Sergievskaya, Anastasiya; El Mel, Abdel-Aziz; Fucikova, Anna; Antunes Corrêa, Cinthia; Vesely, Jozef; Duverger-Nédellec, Elen; Cornil, David; Cornil, Jérôme; Tessier, Pierre-Yves; Dopita, Milan; Konstantinidis, Stephanos (Nanotechnology, 2020)
Effective methods for the synthesis of high-purity nanoparticles (NPs) have been extensively studied for a few decades. Among others, cold plasma-based sputtering metals onto a liquid substrate appears to be a very promising technique for the synthesis of high-purity NPs. The process enables the production of very small NPs without using any toxic reagents and complex chemical synthesis routes, and enables the synthesis of alloy NPs which can be the first step towards the formation of porous NPs. In this paper, the synthesis of gold-copper alloy NPs has been performed by co-sputtering gold and copper targets over pentaerythritol ethoxylate. The resulting solutions contain a mixture of gold, copper oxide, and alloy NPs having a radius of few angstroms. The annealing of these NPs, inside the solution, has been performed in order to increase their size and further induce the dealloying of the Au-Cu NPs. The resulting NPs exhibit either a nanoporous structure or are self-organized in an agglomerate of small NPs.Effective methods for the synthesis of high-purity nanoparticles (NPs) have been extensively studied for a few decades. Among others, cold plasma-based sputtering metals onto a liquid substrate appears to be a very promising technique for the synthesis of high-purity NPs. The process enables the production of very small NPs without using any toxic reagents and complex chemical synthesis routes, and enables the synthesis of alloy NPs which can be the first step towards the formation of porous NPs. In this paper, the synthesis of gold-copper alloy NPs has been performed by co-sputtering gold and copper targets over pentaerythritol ethoxylate. The resulting solutions contain a mixture of gold, copper oxide, and alloy NPs having a radius of few angstroms. The annealing of these NPs, inside the solution, has been performed in order to increase their size and further induce the dealloying of the Au-Cu NPs. The resulting NPs exhibit either a nanoporous structure or are self-organized in an agglomerate of small NPs.